Perbandingan Hukum Informed Consent Indonesia dan Amerika Serikat - Ida Sugiarti (Syiar Hukum, 2010)
Perhaps the most important development in patients’ rights has been that in Indonesia and the United States regarding the doctrine of informed consent. Embracing the Continental European legal system, the doctrine of informed consent in Indonesia is articulated in  Law No. 36 of 2009 on Health, Government Regulation No.32 of 1996 on Health Worker, Law No.29 of 2004 on Medical Practice, and Law No. 8 of 1999 on Consumer Protection. It is also specifically regulated by Health Ministerial Decree No. 29 of 2008 regarding Medical Action Approval.  This doctrine requires physicians to share certain information with patients before asking for their consent to treatment. The Court in  the United States of America used the term of informed consent to describe the physicians obligations to provide information. The legal consequences if informed consent is not given, it is considered  as an act of abuse (intentionally) to the patient. According to Rule of law in the United States  that physicians have to open all the information about all the necessary facts, so that patients can determine appropriate treatment options. Tort Law in Anglo-Saxon legal system, similar to "act against the law" in the Continental European legal system. This article examines a comparative study of informed consent in the Indonesian Health Laws and regulations and those of the United States.